Analysis of a Low-Earth Orbit Satellite Downlink Considering Antenna Radiation Patterns and Space Environment in Interference Situations - Kang, Eunjung; Yang, Junmo; Park, Young Ju; Kim, Jung Hoon; Shin, Wook Hyeon; Park, Yong Bae; Choo, Hosung (Remote Sensing, 2023)
This paper investigates a low-Earth orbit (LEO) satellite downlink for high-speed data communication in interference situations. A choke ring horn type antenna is used as the data transmitting antenna with an isoflux pattern in the LEO satellite, which has a beam coverage of ±51.6° and a bore-sight gain of 4.4 dBi at 8 GHz. The receiving antenna on the ground station is a parabolic type antenna with a diameter of 11.3 m, and it has a half-power beam width (HPBW) of 0.2° with a maximum gain of 59 dBi at 8 GHz. The jamming-to-signal ratio (J/S) is calculated assuming that the LEO satellite transmits signals to the ground station, and an elevation angle of the interference source varies from 0° to 90° at an altitude of 10 km. Applying antenna characteristics, such as HPBWs and side lobes, to the calculated space wave path loss makes it possible to predict the J/S results according to the location of the interference source and the satellite. The results show that it is necessary to consider the space environment to accurately analyze the LEO satellite downlink, especially at the low elevation angle of the satellite.
Keywords: Antennas radiation patterns; Ground stations; Interference situation; Interference sources; J/S; Link budgets; Low earth orbit satellites; Satellite downlink; Space environment; Unwanted interference source; antenna radiation patterns; interference situation; J/S; LEO satellite; link budget; space environment; unwanted interference source; wave propagation